Classifying Christians : ethnography, heresiology, and the limits of knowledge in Late Antiquity - Berzon, Todd S., 1983- (University of California Press, 2016)
"Classifying Christians investigates the ways in which late antique Christian heresiologists (150-450 C.E.) produced polemical ethnographies and presented their ethnographic dispositions in theological terms. The book demonstrates how the rituals, doctrines, customs, and origins of heretics functioned to map and delimit the composition of the Christian world and the world at large. Heresiology was about understanding human difference and organizing knowledge of it"--Provided by publisher